Impact of Crystallisation processes on depth profile formation in sol-gel PbZr0.52Ti0.48O3 thin films - Aulika, I.; Mergen, S.; Bencan, A.; Zhang, Qi; Dejneka, A.; Kosec, M.; Kundzins, K.; Demarchi, D.; Civera, P. (Maney Publishing, 2013)
This study revealed the influence of crystallisation processes on the homogeneity of the sol-gel PbZr0.52Ti0.48O3 thin films, allowing identification and further optimisation of thin film performance. Crystallisation processes determine the optical gradient appearance, irrespective of the chemical solvents used in this work. X-ray differaction analysis showed that a refractive index gradient was apparent in the samples which had dominant (001)/(100) orientation and significant change of lattice parameters with thickness.